2021
DOI: 10.1016/j.radcr.2021.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MRI brain findings in the R1349Q pathogenic variant of CACNA1A

Abstract: Pathogenic CACNA1A gene variants are associated with a spectrum of disorders including migraine with or without hemiplegia, ataxia, epilepsy, and developmental disability. We present a case of a pathogenic variant (c.4046G>A, p.R1349Q) in the CACNA1A gene associated with a clinical phenotype of global developmental delay, left hemiparesis, epilepsy, and stroke-like episodes. Longitudinal neuroimaging demonstrates hemispheric encephalomalacia with mismatched perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…She presented with significant ischemic injury after a head trauma at the age of 3.5 years. This same variant was later seen in children with strokes as reported by Ho et al 11 and Le Roux et al 10 The next patient described in literature was a 4-year-old girl who was found to have a heterozygous, de novo variant, c.5075T>A (p.L1692Q) in the CACNA1A gene. 8 She presented with ischemic injury secondary to fever as young as 6 weeks old.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…She presented with significant ischemic injury after a head trauma at the age of 3.5 years. This same variant was later seen in children with strokes as reported by Ho et al 11 and Le Roux et al 10 The next patient described in literature was a 4-year-old girl who was found to have a heterozygous, de novo variant, c.5075T>A (p.L1692Q) in the CACNA1A gene. 8 She presented with ischemic injury secondary to fever as young as 6 weeks old.…”
Section: Discussionsupporting
confidence: 65%
“…It is primarily used in the pediatric population for the treatment of supraventricular tachycardia, but in adult populations it is primarily used as an anti-hypertensive agent, and as a class, calcium channel blockers have been shown to reduce the risk of stroke in hypertensive populations. 11 Verapamil can also be used off-label for prevention of migraines, cluster headaches, and hemiplegic migraines, and is often used by neurointerventionalists for the treatment of cerebral vasospasm. [17][18][19][20] Verapamil was successfully used in an episode of stroke after head trauma and seizures in the patient described by Knierim et al 9 In fact, many of the reported cases of ischemic injury associated with this gene mutation have been treated with verapamil with either unchanged or improved clinical outcomes (including our own, whom were treated with 0.2-0.3mg/kg/day divided into three doses daily).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 83 variants reported to relate to epilepsy ( Imbrici et al, 2004 ; Kors et al, 2004 ; Rajakulendran et al, 2010 ; Zangaladze et al, 2010 ; Yamazaki et al, 2011 ; Damaj et al, 2015 ; Byers et al, 2016 ; Reinson et al, 2016 ; Du et al, 2017 ; Lv et al, 2017 ; Epperson et al, 2018 ; Hayashida et al, 2018 ; Kothur et al, 2018 ; Lee et al, 2018 ; Angelini et al, 2019 ; Jiang et al, 2019 ; Yamamoto et al, 2019 ; Gauquelin et al, 2020 ; Gudenkauf et al, 2020 ; Mitta et al, 2020 ; Stendel et al, 2020 ; Zhang et al, 2020 ; Ho et al, 2021 ; Le Roux et al, 2021 ; Stubberud et al, 2021 ; Verriello et al, 2021 ; Alehabib et al, 2022 ; Bolte et al, 2022 ; Hommersom et al, 2022 ; Krygier et al, 2022 ; Li et al, 2022 ; Lipman et al, 2022 ; Niu X. et al, 2022 ; Niu Y. et al, 2022 ) as shown in Supplementary Table 2 . The majority of the variants were missense (77.20%) followed by nonsense (8.80%) as shown in Figure 1A .…”
Section: Resultsmentioning
confidence: 99%